STUDI PENURUNAN KONSENTRASI NIKEL DAN TEMBAGA PADA LIMBAH CAIR ELEKTROPLATING DENGAN METODE ELEKTROKOAGULASI - Rachmanita Nofitasari; Ganjar Samudro; Junaidi Junaidi (Jurnal Teknik Lingkungan, 2013)
Abstract Electroplating industrial wastewater containing heavy metals that are harmful so that need treatment in order to minimize impact on the environment. Most industries treat their wastewater by coagulation - flocculation. It is easy in the processing but the cost and the resulting large amount of mud, especially in metal-based industries. The experiments were conducted in batches of 1 liter for 120 minutes, direct current of 5 A and a voltage of 3 V at current densities of 40, 50, 60, and 70 mA/cm2 and type electrode Aluminum and Iron. From the experimental values obtained electrocoagulation efficiency is 95% Ni and Cu were 98% in current density 70mA/cm. Comparison between electrocoagulation and coagulation do to get a new alternative technology in electroplating wastewater treatment. In terms of cost and processing electrocoagulation technique has many advantages than coagulation. Therefore the best treatment alternative selection is electrocoagulation